Dynamics of degradation of new samples of membrane coating based on cellulose polymers - Lipatov, Viacheslav Alexandrovich; Inarkhov, Mikhael Alexandrovich; Yarmamedov, Dmitriy Mutalifovich; Poddelkova, Anna Jurievna; Governor, Samuel Bisilki; Ankrah, Prince Twumasi (International Surgery Journal, 2016)
Background:The use of polymeric coating implants is a promising way of preventing adhesion disease and its related complications in the peritoneum. In this paper, the dynamics of degradation of new samples were studied in an in vitro experiment. A sample was then chosen which is potentially suitable for further research in an in vivo experiment. Methods: In the research, 7 different samples of polymeric coating were studied viz. No. 81 MN, No 82. MN, No. 83 MN, No. 84 MN, No. 85 MN, No. 86 MN and No. 87 MN - developed by Lintex, LCC (St. Petersburg) together with the department of Operative Surgery and Topographical Anatomy named after A.D. Myasnеkov of Kursk State Medical University. The samples were differentiated by subjecting them to different technological processing of temperature, and chemical agents etc. Results:In the course of the experiment, it was discovered that the rate of degradation of the polymeric coating implants depended on their processing methods. Conclusions:Membranes that quickly undergo degradation cannot be used for prophylaxis of complications caused by surgical interventions.